2012
DOI: 10.1038/cdd.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

CD147 induces UPR to inhibit apoptosis and chemosensitivity by increasing the transcription of Bip in hepatocellular carcinoma

Abstract: The unfolded protein response (UPR) is generally activated in solid tumors and results in tumor cell anti-apoptosis and drug resistance. However, tumor-specific UPR transducers are largely unknown. In the present study, we identified CD147, a cancer biomarker, as an UPR inducer in hepatocellular carcinoma (HCC). The expression of the major UPR target, Bip, was found to be positively associated with CD147 in human hepatoma tissues. By phosphorylating FAK and Src, CD147-enhanced TFII-I tyrosine phosphorylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 36 publications
(46 reference statements)
1
69
0
Order By: Relevance
“…It has been reported that TFII-I undergoes a Src kinase-dependent phosphorylation and nuclear localization in response to growth factor signaling. 35,42 It has also been reported that ERK1/2, which is a downstream target of Ras, regulates the activity of TFII-I by direct phosphorylation. ERK1/2 forms an in vivo complex with TFII-I and dominant-negative Ras abrogates this interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TFII-I undergoes a Src kinase-dependent phosphorylation and nuclear localization in response to growth factor signaling. 35,42 It has also been reported that ERK1/2, which is a downstream target of Ras, regulates the activity of TFII-I by direct phosphorylation. ERK1/2 forms an in vivo complex with TFII-I and dominant-negative Ras abrogates this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…35 Briefly, full-length TFII-I was PCR-amplified using an Advantage-GC Genomic PCR kit (Clontech, Palo Alto, CA, USA), and the primers (synthesized by the Shanghai Sangon) were designed as follows: forward primer, 5 0 -TTG GATCCCGCCCCCCCGCTTCCCCGCACGCGC-3 0 (BamHI) and reverse primer, 5 0 -GCTCTAGAAAACTATGCCGTCAC AG-3 0 (XbaI). The products were confirmed by sequencing (Shanghai Sangon, Shanghai, China) and then cloned into the pcDNA3.1 vector (Promega, Madison, WI, USA).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…So far, several studies have identified the important role played by various genetic factors in the progression of HCC (Villanueva et al, 2010;Tang et al, 2012;Marquardt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…GRP78 expression is primarily regulated at the transcriptional level, mediated by multiple copies of the ER stress response element within the GRP78 promoter region (28). We showed by RT-qPCR that GRP78 mRNA levels were decreased by inhibition of MEK/ERK in the presence or absence of TM, indicating that the MEK/ERK pathway may participate in regulation of GRP78 transcription.…”
Section: Discussionmentioning
confidence: 79%